Lactobacillus casei modulates the inflammation-coagulation interaction in a pneumococcal pneumonia experimental model - Alvarez Susana; Zelaya Hortensia; Villena Julio; Haro Cecilia; Agüero Graciela (BMC, 2009)
Abstract Background We have previously demonstrated that Lactobacillus casei CRL 431 administration improved the resistance to pneumococcal infection in a mouse model. Methods This study examined the effects of the oral administration of Lactobacillus casei CRL 431 (L. casei) on the activation of coagulation and fibrinolytic systems as well as their inhibitors during a Streptococcus pneumoniae infection in mice. Results The alveolo-capillary membrane was damaged and the coagulation system was also activated by the infection. As a consequence, we could see fibrin(ogen) deposits in lung histological slices, increased levels of thrombin-antithrombin complex (TATc) in bronchoalveolar lavage (BAL) and plasma, decrease in prothrombin activity (PT) and prolonged activated partial thromboplastin time test (APTT) values. Factor VII (FVII) and factor X (FX) were decreased in plasma, whereas fibrinogen (F) and factor VIII (FVIII) were increased. The low levels of protein C (PC) in BAL and plasma proved damage on inhibitory activity. The infected animals showed reduced fibrinolytic activity, evidenced by an increase in plasminogen activation inhibitor-1 (PAI-1) in BAL and plasma. The pathogen induced an increase of TNF-α, IL-1β and IL-6 in BAL and serum a few hours after challenge followed by a significant decrease until the end of the assayed period. IL-4 and IL-10 in BAL and serum were also augmented, especially at the end of the experiment. The animals treated with L. casei showed an improvement of alveolo-capillary membrane, lower fibrin(ogen) deposits in lung and decrease in TATc. APTT test and PT, FVII and FX activity were normalized. L. casei group showed lower F levels than control during whole experiment. In the present study no effect of L. casei on the recovery of the inhibitory activity was detected. However, L. casei was effective in reducing PAI-1 levels in BAL and in increasing anti-inflammatory ILs concentration. Conclusion L. casei proved effective to regulate coagulation activation and fibrinolysis inhibition during infection, leading to a decrease in fibrin deposits in lung. This protective effect of L. casei would be mediated by the induction of higher levels of IL-4 and IL-10 which could regulate the anti-inflammatory, procoagulant and antifibrinolytic effects of TNF-α, IL-1β and IL-6.